2014
DOI: 10.1111/peps.12082
|View full text |Cite
|
Sign up to set email alerts
|

Are Telecommuters Remotely Good Citizens? Unpacking Telecommuting's Effects on Performance Via I‐Deals and Job Resources

Abstract: Despite their widespread adoption, concerns remain that virtual work arrangements can harm employee job performance and citizenship behavior. Does telecommuting really hamper these critical dimensions of employee effectiveness? To answer this question, we develop a theoretical framework linking telecommuting to task and contextual performance via a dual set of mechanisms-reflecting proposed effects of i-deals and job resources. Further, we propose that the meaning of and outcomes from these paths depend on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
189
2
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(203 citation statements)
references
References 94 publications
(141 reference statements)
5
189
2
7
Order By: Relevance
“…Virtual work can reduce work stress (Raghuram & Wiesenfeld 2004) and increase feelings of autonomy (Kelliher & Anderson 2008), organizational commitment (Hunton & Norman 2010), job satisfaction (Virick et al 2010), and job performance (including extrarole behaviors) (Bloom et al 2015, Gajendran et al 2015, Gajendran & Harrison 2007. One meta-analysis found that telecommuting reduces work-family conflict by helping workers juggle professional and personal work (Gajendran & Harrison 2007).…”
Section: Flexibility In Where Work Is Accomplishedmentioning
confidence: 99%
See 1 more Smart Citation
“…Virtual work can reduce work stress (Raghuram & Wiesenfeld 2004) and increase feelings of autonomy (Kelliher & Anderson 2008), organizational commitment (Hunton & Norman 2010), job satisfaction (Virick et al 2010), and job performance (including extrarole behaviors) (Bloom et al 2015, Gajendran et al 2015, Gajendran & Harrison 2007. One meta-analysis found that telecommuting reduces work-family conflict by helping workers juggle professional and personal work (Gajendran & Harrison 2007).…”
Section: Flexibility In Where Work Is Accomplishedmentioning
confidence: 99%
“…These include getting to choose whether (i.e., having a choice) and when (i.e., scheduling flexibility) to work remotely (Allen et al 2015) as well as having good relationships with bosses/coworkers (Gajendran et al 2015, Gajendran & Harrison 2007 and working virtually in moderation (Allen et al 2015). Remote workers are able to do more in less time because they have higher levels of work intensity (Kelliher & Anderson 2010).…”
Section: Flexibility In Where Work Is Accomplishedmentioning
confidence: 99%
“…Recent research on i‐deals emphasizes that they may not always deliver the expected outcomes for recipients (Bal & Rousseau, ). Researchers have examined the role of coworkers (Lai, Rousseau, & Chang, ; Liu, Lee, Hui, Kwan, & Wu, ; Marescaux, De Winne, & Sels, ) and supervisors (Anand et al, ; Gajendran, Harrison, & Delaney‐Klinger, ) to understand when the effects of i‐deals are not favorable for their recipients. However, to our knowledge, researchers have not yet paid attention to the potentially detrimental role of contextual factors beyond the actors involved in i‐deal making.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…FWDs result in both positive and negative effects for employees, such as enhanced autonomy and work intensification (Towers et al ., ; Gajendran and Harrison, ; Chesley, ; Kelliher and Anderson, ; Chesley, ; Gajendran et al ., ). Contemporary technology enables employees to access and exchange information efficiently across the boundaries of time and space, affording them greater control over their work during the day (Matusik and Mickel, ; Ten Brummelhuis et al ., ; Cavazotte et al ., ).…”
mentioning
confidence: 97%
“…As these studies confirmed either the existence of FWD‐related challenges or FWD‐related demands, integrating these advantages and challenges in one model help to understand their relative strength in the FWD–employee well‐being relationship. The FWD advantages that are confirmed in the literature include work/life balance (Gajendran and Harrison, ; Kelly et al ., ; Moen et al ., ), job autonomy (Gajendran and Harrison, ; Mazmanian et al ., ; Gajendran et al ., ) and communication effectiveness (Rennecker and Godwin, ; Chesley, ; Ten Brummelhuis et al ., ). The FWD challenges that we find evidence for in the literature consist of interruptions (Fonner and Roloff, ; Chesley, ), unpredictability (Jarvenpaa and Lang, ; Thomas et al ., ; Perlow, ), and work intensification (Towers et al ., ; Chesley, ; Kelliher and Anderson, ).…”
mentioning
confidence: 99%